Analysing the European Union's Tenders Electronic Daily: possibilities and pitfalls. (2018) - Prier, Eric; Prysmakova, Palina; McCue, Clifford P.
As a public policy tool, the open data movement holds out hope of large payoffs in democratic transparency and accountability. This paper explores the efficacy of the Tenders Electronic Daily or TED open dataset which covers 33 European countries operating at numerous levels of government. While the recent move toward making the TED open data available in a potentially more user-friendly CSV format could have been a milestone in realising a major aspect of the goals of the open data movement, this study demonstrates that the redundant structure of the individual files is extremely difficult to understand in its current form. Moreover, the transparency that may have resulted from this initiative is unlikely to efficiently serve the purposes of public procurement accountability. As a result, the TED open data in CSV format should be approached with an abundance of caution.